2014
DOI: 10.3389/fnbeh.2014.00276
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazine analogs are active components of wolf urine that induce avoidance and fear-related behaviors in deer

Abstract: Our previous studies indicated that a cocktail of pyrazine analogs, identified in wolf urine, induced avoidance and fear behaviors in mice. The effects of the pyrazine cocktail on Hokkaido deer (Cervus nippon yesoensis) were investigated in field bioassays at a deer park in Hokkaido, Japan. A set of feeding bioassay trials tested the effects of the pyrazine cocktail odor on the behavior of the deer located around a feeding area in August and September 2013. This odor effectively suppressed the approach of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…This would be in accordance with previous studies (Osada et al 2014, S anchez-Gonz alez et al 2017). Voles would feel safer in control and social odor treatments and spend more time in boxes containing those treatments.…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…This would be in accordance with previous studies (Osada et al 2014, S anchez-Gonz alez et al 2017). Voles would feel safer in control and social odor treatments and spend more time in boxes containing those treatments.…”
Section: Introductionsupporting
confidence: 94%
“…In many mammalian prey species, this includes behavioral changes such as freezing, avoidance, and heightened vigilance, but also the ability to detect and correctly recognize the odors emitted by predators, from here on predator odor (PO), which serve as triggers for the adaptive behaviors previously mentioned (Kats and Dill 1998, Dielenberg and McGregor 2001, Sundell and Yl€ onen 2004, Conover 2007, Osada et al 2014, Apfelbach et al 2015, Sievert and Laska 2016. In many mammalian prey species, this includes behavioral changes such as freezing, avoidance, and heightened vigilance, but also the ability to detect and correctly recognize the odors emitted by predators, from here on predator odor (PO), which serve as triggers for the adaptive behaviors previously mentioned (Kats and Dill 1998, Dielenberg and McGregor 2001, Sundell and Yl€ onen 2004, Conover 2007, Osada et al 2014, Apfelbach et al 2015, Sievert and Laska 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, natural predator odors elicit species-specific fear behaviors (e.g. “tail-flag, flight and jump behaviors in deer exposed to wolf urine; Osada et al, 2014; for review see Apfelbach et al, 2005). Fear behaviors associated with exposure to predator odors in animals represent an innate response conserved through evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, black‐tailed deer ( Odocoileus hemionus columbianus ) can discriminate between the scent of dangerous predators (wolves, Canis lupus ) that have been absent for over 100 years and cues from less‐dangerous predators (black bear, Ursus americanos ) that are currently present (Chamaillé‐Jammes et al., ). Another study (Osada, Miyazono & Kashiwayanagi, ) showed that Hokkaido deer ( Cervus nippon ) would respond to scents of Japanese wolves ( Canis lupus hodophilax ), even though this predator had been extinct locally for about 100 years. Both studies seem to indicate that any phyletic knowledge might persist for long periods of time.…”
Section: Neurobiological Mechanisms Underlying Prey Responsesmentioning
confidence: 99%